Hierarchical Fe-Mn binary metal oxide core-shell nano-polyhedron as a bifunctional electrocatalyst for efficient water splitting - Li, Yun-Wu; Su, Shi-Kun; Yue, Cai-Zhen; Shu, Jun; Zhang, Peng-Fang; Du, Fang-Hui; Wang, Su-Na; Ma, Hui-Yan; Yin, Jie; Shao, Xin (Dalton transactions : an international journal of inorganic chemistry, 2021)
Electrochemical water splitting is convinced as one of the most promising solutions to combat the energy crisis. The exploitation of efficient hydrogen and oxygen evolution reaction (HER/OER) bifunctional electrocatalysts is undoubtedly a vital spark yet challenging for imperative green sustainable energy. Herein, through introducing a simple pH regulated redox reaction into a tractable hydrothermal procedure, a hierarchical Fe 3 O 4 @MnO x binary metal oxide core-shell nano-polyhedron was designed by evolving MnO x wrapped Fe 3 O 4 . The MnO x effectively prevents the agglomeration and surface oxidation of Fe 3 O 4 nano-particles and increases the electrochemically active sites. Benefiting from the generous active sites and synergistic effects of Fe 3 O 4 and MnO x , the Fe 3 O 4 @MnO x -NF nanocomposite implements efficient HER/OER bifunctional electrocatalytic performance and overall water splitting. As a result, hierarchical Fe 3 O 4 @MnO x only requires a low HER/OER overpotential of 242/188 mV to deliver 10 mA cm −2 , a small Tafel slope of 116.4/77.6 mV dec −1 , combining a long-term cyclability of 5 h. Impressively, by applying Fe 3 O 4 @MnO x as an independent cathode and anode, the overall water splitting cell supplies a competitive voltage of 1.64 V to achieve 10 mA cm −2 and super long cyclability of 80 h. These results reveal that this material is a promising candidate for practical water electrolysis application. A hierarchical Fe 3 O 4 @MnO x binary metal oxide core-shell nano-polyhedron executes excellent HER/OER bifunctional electrocatalytic activities due to abundant active sites and the synergistic effects of each component.